Functional and Evolutionary Characterization of the NSP6 Protein in SARS-CoV-2 Omicron Variants - Joyhare Barbosa Souza; Samir Mansour Moraes Casseb (SynBio, 2025)
The SARS-CoV-2 virus, which causes COVID-19, has rapidly evolved, producing highly transmissible variants like Omicron. Non-structural protein 6 (NSP6) is essential for viral replication and immune evasion. This study analyzed the NSP6 protein of the Omicron variant, focusing on conserved motifs, mutations, and residual properties to better understand its structure, function, and potential for immune evasion. Sequences from humans in South America were obtained from GISAID and aligned using Clustal Omega 1.2.4, with mutations identified by a Python 3 algorithm and conserved motifs detected using the MEME tool. Sequence diversity was assessed with Shannon’s entropy, while hydrophilicity, flexibility, accessibility, and antigenicity were analyzed using EMBOSS PEPSTATS and Expasy’s ProtScale tools. Phylogenetic analysis was performed with IQ-TREE software. Analysis of 161 NSP6 protein sequences revealed significant divergence from the reference sequence, with mutations proximal to conserved regions indicating potential functional and structural changes. The analysis also identified distinct hydrophobic and hydrophilic regions, with specific amino acid positions showing high flexibility and antigenicity. Phylogenetic analysis identified three clades with varying degrees of similarity to the reference sequence. This comprehensive study of the NSP6 protein in the Omicron variant provides insights into its role in viral replication and immune evasion, contributing to the development of targeted interventions against COVID-19.